Can sports events improve residents’ psychic income? - Cai, Jie (Frontiers in Psychology, 2022)
To better understand the positive impact of sports events on host cities, this study uses social capital and social identity theories combined with structural equation modeling (SEM) to explain the psychic income that sports events may bring to residents. The investigation and analysis of the Qingdao Marathon in 2021 show that (1) sports events can generate social capital; (2) social capital can positively influence social identity; and (3) social identity can significantly impact event excitement, city attachment, and city pride in psychic income.